PREVALENCE OF DEPRESSION IN HOSPITALIZED PATIENTS OF PULMONARY TUBERCULOSIS - Ali, Gulzar; Khan, Imran; Amir, Muhammad; Khan, Malik Nadeem Azam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find the prevalence of depression in admitted patients of pulmonary tuberculosis.Study Design: Cross-sectional study.Place and Duration of Study: Tuberculosis centre, Pak Emirates Military Hospital Rawalpindi and Medicinedepartment Combined Military Hospital Peshawar, from Dec 2017 to May 2018.Methodology: One hundred and six patients of both genders admitted due to pulmonary tuberculosis for more than 2 weeks were taken into study. Individuals on treatment for depression before diagnosis of tuberculosis on medical records and patients with chronic debilitating diseases liable to depression were excluded. All patients were interviewed and scored on Hamilton Depression Rating Scale. Data was noted on especially designed proforma. Statistical analysis was done on SPSS-22.Results: Mean age of the patients was 37.452 ± 9.26 years with range from 20 to 60 years. Mean duration oftuberculosis was 4.283 ± 1.21 months and mean duration of hospitalization was 3.584 ± 0.65 weeks while meanweight was 70.839 ± 8.85 Kg. Majority of the patients were male 54 (50.9%) and married 79 (74.5%). Depressionwas seen in 45 (42.5%) patients.Conclusion: The effects of chronic diseases such as tuberculosis are not only physical but also include mentalhealth dysfunction which can lead to poor drug compliance and ultimately drug resistance. In our studydepression was recorded in 42.5% of patients hospitalized for treatment of tuberculosis. Thus, all admittedpatients of tuberculosis should be screened for depression and managed in collaboration with psychiatrist.Keywords: , ,